Platelet-Derived Extracellular Vesicles as Target of Antiplatelet Agents. What Is the Evidence? - Taus, Francesco; Meneguzzi, Alessandra; Castelli, Marco; Minuz, Pietro (Frontiers in Pharmacology, 2019)
Platelet-derived extracellular vesicles (often referred to as microparticles in the field of cardiovascular disease) have been identified as effector in the atherothrombotic process, therefore representing a target of pharmacological intervention of potential interest. In spite of that, limited evidence is so far available concerning the effects of antiplatelet agents on the release of platelet derived extracellular vesicles. In the present narrative review the mechanisms leading to vesiculation in platelets and the mechanisms implicated will be discuss. This will be followed by a summary of the present evidence concerning the effects of antiplatelet agents under experimental conditions and in clinical settings.